Effects of flow history on extensional rheological properties of wormlike micelle solution - Jang, In Hyuk; Lee, Won Jun; Jin, Daekwon; Kim, Ju Min (RSC Advances, 2022)
A wormlike micelle (WLM) solution is a complex fluid that forms when the surfactant concentration is high. It has rheological properties similar to those of polymer solutions. However, unlike polymer molecules, WLM chains possess the dynamic microstructure that can be reversibly broken and reassembled in flows. Therefore, the rheological properties and flow behavior of WLM solutions have attracted much attention owing to their unique dynamic microstructures. However, the effects of the flow history on the extensional rheological properties of WLM solutions remain unclear. In this study, the change in the extensional rheological properties of WLM solutions depending upon on their shear flow histories was investigated by combining the dripping-onto-substrate/capillary break-up extensional rheometry technique with a compressed gas flow (stop-flow) control method. This approach precisely controls the shear flow histories of the WLM solutions. The results revealed that the shear flow history has a substantial impact on elongational rheological properties such as relaxation time. They also showed that the effects of the characteristic shear rate are highly dependent on the surfactant concentration. We expect that the current findings can be applied to understand the extensional rheological properties of complex fluids in industrially relevant processes such as coating and printing.
Keywords: Complex fluids; Dynamic microstructures; Flow history; Micelle chains; Micelle solution; Polymer molecule; Rheological flow; Rheological property; Surfactant concentrations; Wormlike micelle